Inovasi Manajemen Pemasaran : Suatu Kajian Literatur - Edi Irawan (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2024)
The aim of this research is to discuss innovation in marketing management of village Micro, Small and Medium Enterprises through social customer relationship management (SCRM), digitalization and technological guidance assistance. The method used is a systematic literature review method. Systematic literature reviews are used for the process of identifying, evaluating and interpreting research results relevant to research objectives that include research questions, topic areas and related phenomena. One of the main reasons for conducting qualitative research is because the research is exploratory in nature. Based on the discussion above, it can be concluded that social customer relationship management is defined as a business philosophy and strategy, supported by technology platforms, business rules, processes and social characteristics, which are designed to involve customers in collaborative conversations to deliver mutually beneficial value in a trusted and transparent business environment. Micro, small and medium enterprises need to maintain good relationships with customers and increase their loyalty through knowledge and fulfilling customer needs quickly and precisely. One of the keys for micro, small and medium enterprises to survive in today's competitive business world is through business digitalization, where micro, small and medium enterprises can take advantage of this to develop business performance. Government policy in the form of technical guidance training in the form of training for micro, small and medium enterprises is expected to strengthen the relationship between entrepreneurial marketing and marketing performance.